STRATEGI PEMERINTAH DESA DALAM MENJAGA KESTABILAN EKONOMI MASYARAKAT DESA DI TENGAH PANDEMI COVID 19 (SUATU STUDI DI DESA PUSUNGE KECAMATAN TABUKAN UTARA KABUPATEN KEPULAUAN SANGIHE) - LEGESANG, DESTRINA; TAMPI, GUSTAAF; TAMPONGANGOY, DEYSI (Sam Ratulangi University, 2021)
This study aims to determine the village government's strategy in maintaining the economic stability of ruralcommunities in the midst of the COVID 19 pandemic. This study uses a qualitative descriptive researchmethod. The theory used in this research is the theory of strategic management indicators from Freed R.David which includes strategy formulation, strategy implementation and strategy evaluation. The researchinformants were the head of Pusunge Village, the Village Secretary, the Head of Environment 2, and a totalof 5 people. Data collection techniques used by researchers are observation, interviews and documentation.The results of this study indicate that the strategy taken by the village government has been well realized byproviding seeds to the community that can help maintain the economic stability of the community in the midstof the COVID-19 pandemic. implementation of strategies taken by village governments and communities whostill do not comply with health protocols.Keywords: Strategy, Economic Stability